Startegi Pengelolaan Wakaf Produktif dalam Pemberdayaan Masyarakat Islam di Lembaga Lampung Al Qur’an Center (LAC) Bandar Lampung - Fauzi Nadziiran Haq; M. Bahri Ghazali; Khairullah Khairullah; Jasmadi Jasmadi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
The issue of education financing in Indonesia, particularly in Islamic educational institutions, remains a challenge even though the national education budget has reached 20%. High operational costs, uneven budget distribution, and limited resources are obstacles to improving the quality of education and empowering the Islamic community. In this case, productive waqf presents itself as a sharia economic instrument that has the potential to support sustainable education financing and community development. This study aims to analyze the management strategy of productive waqf in empowering the Islamic community at the Lampung Al-Qur'an Center (LAC) and review it from the perspective of Islamic jurisprudence (fiqh muamalah) and waqf management. The study used a field method with a descriptive qualitative approach through interviews, observation, and documentation. The theories used are George R. Terry's management theory and Jim Ife's community empowerment theory. The results show that the productive waqf management strategy at LAC is carried out through waqf fund collection, management of Al-Qur'an education, socio-religious development, and community empowerment programs based on Islamic education. This management contributes to improving the quality of education, strengthening Islamic values, and social and economic empowerment of the community. From a muamalah jurisprudence perspective, the practice of productive waqf in LAC has a strong sharia basis because it is oriented towards the welfare of the community and the sustainability of the waqf's benefits. Thus, productive waqf in LAC can be an alternative for financing Islamic education and sustainable community empowerment.